Tell me what you like : an honest discussion of sex and intimacy after sexual assault - Simon, Katie (Author of Tell me what you like) (Citadel Press, Kensington Publishing Corp., 2025)
"Over a decade ago, Katie Simon began seeking out stories of people who faced sexual challenges after sexual trauma-just as she did. Simon interviewed dozens of survivors, and her investigation yielded diverse responses from people of all backgrounds, ultimately confirming that there is no single path toward healing. Simon's research led her to life-changing findings that sexual assault survivors most want to know about, including coping with trauma triggers and traumatic stress symptoms such as anxiety, depression, physical pain, and flashbacks. From embodied consent to self-pleasure, sexual regret, breakups, and beyond, you'll find answers to all your questions about how sexual trauma affects sex and relationships within these pages, in stories told by survivors who've actually been there. Millions of survivors across the United States are treated as irreparably broken. Simon offers a positive approach to healing based on empathy and community--and the understanding and tools to navigate trauma and cultivate the sex lives we desire and deserve. The narratives Simon has gathered break down the potential obstacles to rebuilding post-assault, and offer multiple paths forward with optimistic, new approaches to sex after sexual assault. Packed with insights, stories, and advice, this invaluable guide reimagines what sex can look like--not only for survivors, but for all of us"--